The Common-Law Response to the Accident Compensation Scheme - Duffy, Ailsa (Victoria University of Wellington Law Review, 2003)
In a scheme that began with rejecting common law, the reappearance of civil litigation on the margins of ACC during the 1980s drew much attention. In line with successive statutory revisions, certain claims (for example, "nervous shock") were excluded from ACC coverage only to be revived within common law. Other claims, including certain types of medical misadventure, were "covered" by ACC but received no benefits in the absence of economic loss, especially as benefit standards were tightened. In addition the bar on compensatory damages for negligence was held not to exclude exemplary damages. This paper explores the vagaries of ACC coverage that reawakened common law during the 1980s and 1990s, with special attention to various health crises involving women.